Field Measurement of Wind Characteristics of Typhoon Muifa on the Shanghai World Financial Center - Y. An; Y. Quan; M. Gu (International Journal of Distributed Sensor Networks)
Field measurement is considered to be the most reliable method to obtain wind characteristics of typhoon, and it is of essential value of further understanding of wind-resistant design of super tall buildings. In this paper, the wind data were recorded atop the Shanghai World Financial Center (SWFC) with a height of 494 m during the whole course of Typhoon Muifa on August 6–8 in 2011. Detailed analysis of the field data is conducted to investigate the characteristics of the typhoon-generated wind including the mean wind speed and direction, turbulence intensities, gust factors, peak factors, turbulence integral length scales, and spectra of fluctuating wind speed. A comparative study between the measured wind characteristics and those previously obtained in the literature is also carried out. It is found that the average values of turbulence intensities, gust factors, and turbulence integral length scales under the condition of Typhoon Muifa are higher than those under monsoon condition atop the SWFC, and Von Karman spectra are suitable to describe of the turbulent kinetic energy distribution at Lujiazui of the Pudong district in Shanghai.